2010
DOI: 10.3133/ofr20101261
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distribution of endangered juvenile Lost River and shortnose suckers in relation to environmental variables in Upper Klamath Lake, Oregon: 2009 annual data summary

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS. For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 5 publications
4
50
0
Order By: Relevance
“…Instead, juvenile suckers captured in Upper Klamath Lake were progressively larger from June to September throughout Upper Klamath Lake and CPUEs decreased in all parts of the lake simultaneously others, 2007a, 2007b;Bottcher and Burdick, 2010). Extensive studies of juvenile sucker distribution indicated that age-0 suckers are habitat generalists in Upper Klamath Lake once they reach about 45 mm SL and, therefore, indicated that mid-to late-summer decreases in CPUEs were not due to fish changing habitats (VanderKooi and others, 2004;others, 2007a, 2007b;Bottcher and Burdick, 2010;Burdick and Hewitt, 2012). Furthermore, age-0 to age-6 Lost River and shortnose suckers have been captured in Clear Lake Reservoir with the same gear as used in Upper Klamath Lake, indicating that gear avoidance cannot completely explain the nearcomplete annual disappearance of juvenile suckers from Upper Klamath Lake (Burdick and others, 2015).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Instead, juvenile suckers captured in Upper Klamath Lake were progressively larger from June to September throughout Upper Klamath Lake and CPUEs decreased in all parts of the lake simultaneously others, 2007a, 2007b;Bottcher and Burdick, 2010). Extensive studies of juvenile sucker distribution indicated that age-0 suckers are habitat generalists in Upper Klamath Lake once they reach about 45 mm SL and, therefore, indicated that mid-to late-summer decreases in CPUEs were not due to fish changing habitats (VanderKooi and others, 2004;others, 2007a, 2007b;Bottcher and Burdick, 2010;Burdick and Hewitt, 2012). Furthermore, age-0 to age-6 Lost River and shortnose suckers have been captured in Clear Lake Reservoir with the same gear as used in Upper Klamath Lake, indicating that gear avoidance cannot completely explain the nearcomplete annual disappearance of juvenile suckers from Upper Klamath Lake (Burdick and others, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Sampling of suckers throughout Upper Klamath Lake, in the lake's tributaries, and near the lake outlet indicate that emigration and reduced susceptibility to gear alone cannot explain the near absence of older juvenile suckers others, 2007a, 2007b;Bottcher and Burdick, 2010). Summertime movement of juvenile suckers along the eastern shore and toward the lake outlet was not detected from July to September during 2002-06 (Hendrixson and others, 2007a), nor was there a shift in abundance of age-0 juvenile suckers from northern and eastern parts of the lake near spawning areas to areas near lake outlets in lakewide sampling from June to September during 2007-09 (Bottcher and Burdick, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations